Transformasi Pembelajaran Melalui AI dan Platform Digital: Inovasi Teknologi Pendidikan - Dani Oktarian; M.Faiz Hakim; M.Minanullah Muhtadi (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to explore the implementation of Artificial Intelligence (AI) and digital platforms in the transformation of learning at Madrasah Tsanawiyah (MTs) Darul Qur’an Singojuruh. Using a case study method with a qualitative approach, this research analyzes the impact of these technologies on student engagement, the effectiveness of independent learning, and the changing role of teachers. The findings show that the use of interactive AI enhances students' motivation, participation, and understanding through personalized and adaptive learning. Additionally, digital platforms support independent learning by providing flexible access and a variety of learning resources. The role of teachers has also shifted from being mere instructors to facilitators who guide and mentor students in developing critical thinking skills and character values. However, challenges related to digital literacy and infrastructure access remain as barriers. This study concludes that technology does not replace teachers but strengthens the educational process holistically, and digital transformation in madrasahs requires continuous support.